2018
DOI: 10.3892/ol.2018.7752
|View full text |Cite
|
Sign up to set email alerts
|

Human sodium iodide transporter gene-mediated imaging and therapy of mouse glioma, comparison between 188Re and 131I

Abstract: Abstract. Novel treatment options are urgently required for patients with glioma who are not effectively treated through standard therapy. Human sodium iodide symporter (hNIS) is a molecular target of certain tumors types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Attempts to increase radioactive retention by co-expression of NIS and exogenous thyroperoxidase [ 35 , 36 , 37 ] have been implemented, but they have produced insufficient synergistic benefits. Enhancement strategies were also developed to increase the dose in situ using either radioactive substrates with higher destructive potential such as the alpha-particle emitter 211 At [ 38 , 39 , 40 ] and the beta-emitting radiometal 188 Re [ 41 , 42 , 43 ] or by various radio-sensitizing approaches [ 34 , 44 , 45 ]. Improving exogenous NIS expression within non-thyroidal neoplasms has also been largely explored through direct protein delivery [46] and various gene transfer strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to increase radioactive retention by co-expression of NIS and exogenous thyroperoxidase [ 35 , 36 , 37 ] have been implemented, but they have produced insufficient synergistic benefits. Enhancement strategies were also developed to increase the dose in situ using either radioactive substrates with higher destructive potential such as the alpha-particle emitter 211 At [ 38 , 39 , 40 ] and the beta-emitting radiometal 188 Re [ 41 , 42 , 43 ] or by various radio-sensitizing approaches [ 34 , 44 , 45 ]. Improving exogenous NIS expression within non-thyroidal neoplasms has also been largely explored through direct protein delivery [46] and various gene transfer strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The blood-brain barrier (BBB), which can block radiotracers and gene vectors, is one reason for the limitations in effective treatment and detection of GBM. Because NIS-mediated radionuclide imaging and therapy do not require complicated radiolabelling procedures, the small-size radionuclides used are able to penetrate the BBB and diffuse into the tumour [44].…”
Section: The Role Of Nis Imaging In Glioblastoma Multiformementioning
confidence: 99%
“…The authors demonstrated the pos-sibility of non-invasive imaging of GBM using by [ 99m Tc] pertechnetate-and [ 123 I]NaI-scintigraphy, and then prolonging the survival time of rats after 131 I therapy. Guo et al [44] published imaging and therapy experiments with 188 Re or 131 I in mice with tumour xenografts injected with the U87 human glioblastoma cell line that had been transfected with a recombinant lentiviral vector containing human NIS in the right armpit. In vivo imaging results, assessed by gamma camera imaging, showed the 188 Re/ 131 I accumulated in the NIS-containing tumours, and effective reduction of the tumour volume was achieved in the 188 Re or 131 I treated mice compared to untreated control mice.…”
Section: The Role Of Nis Imaging In Glioblastoma Multiformementioning
confidence: 99%
“…Still, if the radiation dose of EBRT is higher than 60 Gy, radiation-related necrosis would occur in the normal brain tissue and result in irreversible damage. So, the effect of EBRT is limited by the radiation dose [ 5 ]. Brachytherapy (BT) has also emerged as a promising treatment method for advanced or recurrent GBM.…”
Section: Introductionmentioning
confidence: 99%